Effectiveness of Forest Moratorium Policy Using the EMMIE Framework Approach - Septiani, Wina Arsy; Rahardian, Ramaditya; Latifah, Latifah; Nu'man, Mohamad Hilal; Andri, Yayan (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2025)
The increasing rate of deforestation in Indonesia has become a critical environmental issue that threatens ecological balance and undermines global climate change mitigation efforts. In response, the Indonesian government implemented a permanent forest moratorium policy through Presidential Instruction No. 5 of 2019, aiming to halt the issuance of new permits for primary forest and peatland exploitation. However, its effectiveness at the local level remains questionable, particularly in regions facing strong economic pressures such as Lembang Subdistrict, West Bandung Regency. This study aims to analyze the effectiveness of the forest moratorium policy in Lembang using the EMMIE Framework, which evaluates five dimensions: Effect, Mechanism, Moderators, Implementation, and Economy. Employing a qualitative descriptive approach, data were collected through in-depth interviews with local government officials, community leaders, tourism operators, and residents, complemented by field observations and document analysis. The results reveal that while the moratorium policy has succeeded in stopping the issuance of new forest conversion permits, illegal land use for tourism and commercial purposes continues to occur due to weak law enforcement, overlapping institutional authority, and low community participation. The analysis further shows that economic pressures and the high market value of forest land act as significant drivers of policy violations. From an implementation perspective, the lack of coordination between central and local agencies hinders policy consistency and sustainability. The study concludes that the effectiveness of the forest moratorium policy in Lembang remains limited and recommends strengthening institutional coordination, enhancing community involvement, enforcing stricter supervision, and promoting sustainable livelihood alternatives to balance environmental protection and local economic development.